2006
DOI: 10.1111/j.1600-0765.2005.00863.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐inflammatory properties of enamel matrix derivative in human blood

Abstract: Enamel matrix derivative limits the release of pro-inflammatory cytokines induced by lipopolysaccharide or peptidoglycan in human blood, suggesting that it has anti-inflammatory properties. We propose that this effect of EMD is, at least partly, secondary to an increase in the intracellular levels of cAMP in peripheral blood mononuclear cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
50
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 34 publications
5
50
0
2
Order By: Relevance
“…This finding was in agreement with Myhre et al (19), who showed that EMD administration together with LPS to whole-blood cell cultures does not significantly decrease TNF-a production. Interestingly, in the study of Myhre et al, when cells were exposed to EMD before stimulation with LPS, they produced significantly less TNF-a in comparison to simultaneous administration.…”
Section: Discussionsupporting
confidence: 89%
“…This finding was in agreement with Myhre et al (19), who showed that EMD administration together with LPS to whole-blood cell cultures does not significantly decrease TNF-a production. Interestingly, in the study of Myhre et al, when cells were exposed to EMD before stimulation with LPS, they produced significantly less TNF-a in comparison to simultaneous administration.…”
Section: Discussionsupporting
confidence: 89%
“…These effects result in the suppression of inflammatory reactions and promote wound healing. Recently it has been reported that EMD suppresses the inflammatory cytokine production by immunocytes (27) and contains TGF-␤-like molecules (28). EMD might create a favorable environment for promoting wound healing in the injured pulp tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of the reparative properties of amelogenins have not been fully elucidated, although amelogenins have positive effects on numerous types of mesenchymal cells (Almqvist et al, 2009(Almqvist et al, , 2010Gestrelius et al, 1997;Grayson et al, 2006;Hoang et al, 2002;Lyngstadaas et al, 2001;Mirastschijski et al, 2004;Narani et al, 2007;Reseland et al, 2006;Rincon et al, 2003;Schlueter et al, 2007;Van Der Pauw et al, 2000;Yuan et al, 2003;Zeldich et al, 2007). Moreover, it has been suggested that amelogenins have anti-inflammatory properties indicated in vitro by the attenuation of the lipopolysaccharide (LPS)-and peptidoglycan-induced production of selected pro-inflammatory cytokines by human blood cells (Myhre et al, 2006) and rat monocytes (Sato et al, 2008).…”
Section: Introductionmentioning
confidence: 97%